PENGARUH UMUR BUAH JERUK MANIS (CITRUS AURANTIUM L.) DAN JERUK NIPIS(C. AURANTIFOLIA(CHRISTM.) SWING)TERHADAP KANDUNGAN VITAMIN C - PANGGABEAN, G.; SUNARTO, A. TRI (BERITA BIOLOGI, 1985)
G. PANGGABEAN & A. TRI SUNARTO. 1985.The effect of fruit maturity of sour orange (Citrus aurantium L.) and lime (C. aurantifolia (Christm.) Swing, on vitamin C content. Berita Biologi 3(3):101 - 103. - The effect of fruit maturity on vitamin content were studied on sour orange (C. aurantium) and lime (C. aurantifolia}.In sour orange,vitamin C content of 13-16 weeks were 24-25 mg/100 ml. However, the content of vitamin C decreased according to the maturity of the fruits which at the stage of 26 weeks reached 11.68 mg/100 ml.The vitamin C of lime at the age of 16 - 19 weeks were 8.50 - 9.14, mg/100 ml. The fruits of 25 weeks old contained 26.50 mg/100 ml of the vitamin C. The fruits became over ripe and rotted after 25 weeks.